Influence of pH and solids content on heat-induced changes in structural arrangements of proteins in milk - Tatijana Markoska; Thom Huppertz; Todor Vasiljevic (Mljekarstvo)
Concentrated milk systems can be unstable during heat treatment. In this work, we studied the structural changes in the proteins in skim milk (9, 17 and 25% solids) as a result of pH adjustment to pH 7.5 and heating at 75, 85, 95 100, 110 and 121 °C by Fourier transform infrared spectroscopy (FTIR) and SDS-PAGE. The pH adjustment to 7.5 resulted in some dissociation of caseins to serum, predominately in the 9% total solids samples. Furthermore, pH adjustment resulted in an increase in random structures at all concentration levels, due to protein unfolding. Heat treatment affected greatly the protein composition in the serum phase and induced structural modifications. All milk samples when heated to 110°C exhibited loss of serum β-LG, α-LA and caseins (mainly κ-casein) as a result of heat induced aggregation. The intensity of aggregation increased with concentration factor. The trend appeared similar at 121°C but with larger aggregates. As a concentration factor increased, covalent bonds among newly formed structures appeared to prevail.